RESEPSI HADIS DO’A NABI JELANG PILPRES 2019 (ANALISIS INFORMATIF DAN PERFORMATIF) - Muhammad HS Alwi (IAIN Manado, 2019)
Abstract: Prayer delivered in the context of war by the Prophet Muhammad was prayed by Neno Warisman, but in a totally different context; that is a political context. Prayers originally requesting a victory in Badar war was misled by Neno Warisman to achieve the same victory in the 2019 presidential election contest. Such submission of the same prayer with different contexts breeds various polemics among Indonesian Muslim communities. This article intends to discuss the prayer of the Prophet Muhammad contained in the Hadith regarding the context of Badr war, especially as was narrated by Imam Muslim. The discussion about the Prophet's prayer will be analyzed based on the reception theory which is analyzed informatively and performatively. An informative analysis is an analytical method that focuses on the hadith text by conducting in-depth studies to understand its content. Performative analysis is an analytical method that focuses on the readers of the hadith, examining how a hadith whose content is not well-understood but creates various receptions or attitudes from the readers. Furthermore, for informative analysis, this paper will discuss textual and contextual understanding, and discuss the implications of understanding when the prayer is performed by Neno in Munajat 212. As for performative analysis, this paper will discuss the responses or attitudes of the readers or recipients of the prayer delivered by the Neno Warisman.Keywords: Hadith, the Prophet's prayer, Warisman's prayer, Informative, and performative. Abstrak: Do’a yang disampaikan dalam konteks peperangan oleh Nabi Muhammad, kembali disampaikan oleh Neno Warisman namun dalam konteks berbeda, yakni perpolitikan. Do’a memohon kemenangan dalam perang badar digiring oleh Neno Warisman untuk mencapai kemenangan dalam kontestasi pemilihan umum presiden 2019. Penyampaian do’a yang berbeda konteks ini kemudian memunculkan berbagai polemik dalam lingkungan umat Islam di Indonesia. Tulisan ini hendak mendiskusikan do’a Nabi Muhammad yang terdapat dalam Hadis pada konteks perang Badar tersebut, khususnya yang diriwayatkan oleh Imam Muslim. Diskusi mengenai do’a Nabi akan dianalisis berdasarkan teori resepsi yang dianalisis secara Informatif dan Performatif. Analisis informatif yaitu analisis yang fokus pada teks hadis, yakni melakukan kajian mendalam sehingga menemukan pemahaman atas kandungan hadis. Sementara analisis performatif yaitu analisis yang fokus pada pembaca hadis, bagian ini meneliti bagaimana sebuah hadis yang secara kandungan tidak dipahami tetapi memunculkan resepsi atau sikap dari pembacanya. Selanjutnya, untuk analisis informatif, tulisan ini akan mendiskusikan pemahaman secara tekstual dan kontekstual, serta mendiskusikan implikasi pemahaman ketika do’a tersebut digunakan oleh Neno dalam munajat 212. Adapun analisis performatif, tulisan ini akan mendiskusikan respon atau sikap pembaca atau penerima do’a yang disampaikan oleh Neno Warisman tersebut.Kata Kunci: Hadis, do’a Nabi, do’a Neno Warisman, Informatif, dan performatif.